Emerging and Recurring Data-Driven Storytelling Techniques: Analysis of a Curated Collection of Recent Stories - Stolper, Charles D.; Lee, Bongshin; Henry Riche, Nathalie; Stasko, John (2016)
Storytelling with data is becoming an important component of many fields such as graphic design, the advocacy of causes, and journalism. New techniques for integrating data visualization into narrative stories have now become commonplace. Authors are enabling new reader experiences, such as linking textual narrative and data visualizations through dynamic queries embedded in the text. Novel means of communicating position and navigating within the narrative also have merged, such as utilizing scrolling to advance narration and initiate animations. We advance the study of narrative visualization through an analysis of a curated collection of recent data-driven stories shared on the web. Drawing from the results of this analysis, we present a set of techniques being employed in these examples, organized under four high-level categories that help authors to tell stories in creative ways: communicating narrative and explaining data, linking separated story elements, enhancing structure and navigation, and providing controlled exploration. We describe the benefits of each storytelling technique along with a number of example applications of the ideas through recent data-driven stories. Additionally, we discuss the trends we observed as well as how the field has evolved and grown. Finally, we conclude with a discussion of areas for future research.